Organization and micromorphology of the ovo-spermathecal apparatus in earthworm Eudrilus eugeniae (Crassiclitellata, Eudrilidae) with a particular emphasis on the ovary and ovisac - D. Raś; A. J. Phillips; P. Świątek (The European Zoological Journal, 2025)
The family Eudrilidae is remarkable among other earthworms for the occurrence of internal fertilization. Also, the female reproductive system in this family is unique due to the evolutionary tendency to unify individual elements into a complex system – the ovo-spermathecal apparatus. We performed light and electron microscopy examinations on sexually mature specimens of Eudrilus eugeniae to describe the morphology and internal organization of the female reproductive system in detail. The ovo-spermathecal apparatus comprises three main elements: spermatheca with two subunits (diverticulum and ampoule), ovary with ovo-spermathecal duct, and ovisac with ovisac duct. The ovary appears to be a rudimentary organ containing only oogonia and early meiotic cells. We discover that the clusters of germline cells detach from the ovary and move via the ovo-spermathecal duct toward the spermatheca, where they continue oogenesis to some extent within small outgrowths of the spermathecal wall termed bulges. However, the main organs where oogenesis occurs are ovisacs, which function as the “true” ovary. In addition, ultrastructural analyses show that the germline cells within the ovaries and ovisacs are organized similarly to other earthworms, i.e., they form syncytial cysts. Within the cyst, each clustering cell is connected by a stable intercellular bridge to the central cytoplasmic mass – the cytophore. As oocytes grow, they detach from the cysts, but the rest of the cells stay interconnected and become nurse cells. We also found that the vitelline envelope in E. eugeniae is prominent and complex (a feature unique among other earthworms and clitellates), probably due to internal fertilization. Given all these features, we propose to use the term “Eudrilus”-type of ovary to describe this unusual organization of female gonads (“Eudrilus”-type of ovary = rudimentary ovary + ovisac). We also present the molecular identification of studied E. eugeniae lineage specimens using selected nuclear and mitochondrial DNA sequences.